2020
DOI: 10.35772/ghm.2020.01064
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Brief Coping Orientation to Problem Experienced (Brief COPE) inventory in people living with HIV/AIDS in Vietnam

Abstract: The Brief Coping Orientation to Problem Experienced (Brief COPE) inventory is one of the most widely used instruments in coping research; however, no study has evaluated the psychometric properties of the Brief COPE in the Vietnamese population. This study aimed to validate a culturally appropriate Vietnamese version of the Brief COPE for the evaluation of coping strategies in people living with HIV/AIDS in Vietnam. We translated the Brief COPE into Vietnamese, and it was self-administered among 1,164 HIV-infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 44 publications
(53 reference statements)
1
10
0
Order By: Relevance
“…Fourth, some of the subscales of the Brief COPE showed questionable or poor reliability scores in our study (Cronbach's Alpha: 0.53-0.92). This has also been reported in other studies (51,52) and seems to be a general problem of the questionnaire, which is also reflected in the inconsistent factor structure of the Brief COPE (53). Fifth, although the propensity score matching has several advantages for examining the hypotheses and ensured comparability of our samples, the current dataset does not contain all participants and the representativeness of the two subsamples may have been altered especially in the city sample.…”
Section: Limitationssupporting
confidence: 51%
“…Fourth, some of the subscales of the Brief COPE showed questionable or poor reliability scores in our study (Cronbach's Alpha: 0.53-0.92). This has also been reported in other studies (51,52) and seems to be a general problem of the questionnaire, which is also reflected in the inconsistent factor structure of the Brief COPE (53). Fifth, although the propensity score matching has several advantages for examining the hypotheses and ensured comparability of our samples, the current dataset does not contain all participants and the representativeness of the two subsamples may have been altered especially in the city sample.…”
Section: Limitationssupporting
confidence: 51%
“…Three studies conducted a CFA followed by an EFA when poor fit was identified (Brasileiro et al, 2016; Matsumoto et al, 2020; Su et al, 2015). Two studies (Brasileiro et al, 2016; Matsumoto et al, 2020) used the original 14-factor structure translated to Portuguese and Vietnamese. Su et al (2015) used a previously established three and two-factor model translated into Chinese.…”
Section: Resultsmentioning
confidence: 99%
“…Su et al (2015) used a previously established three and two-factor model translated into Chinese. Two studies used a dispositional version (Brasileiro et al, 2016; Matsumoto et al, 2020) and one used an unspecified format (Su et al, 2015). No items or factors were removed a priori to analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a considerable amount of literature dedicated to testing The Brief COPE Inventory in different environment and countries. The Brief COPE scale was validated in different countries, such as Chile [53], China [57,59,60], Italy [61], France [52,62,63], Malaysia [58] Mexico [56], Serbia [64], Russia [44], Spain [65], Uruguay [50], USA [66], United Arab Emirates [67]; as well as different languages and dialects-Persian [68], Tunisian Arabic [69], Urdu [70], Vietnamese [71], Brazilian and Portuguese [49].…”
Section: Conceptualization Of Copingmentioning
confidence: 99%